No place to call home: the 1807-1857 life writings of Caroline Barnes Crosby, chronicler of outlying Mormon communities - Crosby, Caroline Barnes, 1807-1884, author; Lyman, Edward Leo, editor; Payne, Susan Ward, editor; Ellsworth, S. George, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
Caroline Crosby's life took a wandering course between her 1834 marriage to Jonathan Crosby and conversion to the infant Mormon Church and her departure for her final home, Utah, on New Year's Day, 1858. In the intervening years, she lived in many places but never long enough to set firm roots. Her adherence to a frontier religion on the move kept her moving, even after the church began to settle down in Utah. Despite the impermanence of her situation, perhaps even because of it, Caroline Crosby left a remarkably rich record of her life and travels, thereby telling us not only much about herself and her family but also about times and places of which her documentary record provides a virtually unparalleled view. A notable aspect of her memoirs and journals is what they convey of the character of their author, who, despite the many challenges of transience and poverty she faced, appears to have remained curious, dedicated, observant, and cheerful. From Caroline's home in Canada, she and Jonathan Crosby first went to the headquarters of Joseph Smith's new church in Kirtland, Ohio. She recounts, in a memoir, the early struggles of his followers there. As the church moved west, the Crosbys did as well, but as became characteristic, they did not move immediately with the main body to the center of the religion. For awhile they settled in Indiana, finally reaching the new Mormon center of Nauvoo in 1842. Fleeing Nauvoo with the last of the Mormons in 1846, they spent two years in Iowa and set out for Utah in 1848, the account of which journey is the first of Caroline Crosby's vivid trail journals. The Crosbys were able to rest in Salt Lake City for less than two years before Brigham Young sent them on a church mission to the Society and Austral Islands in the South Pacific. She recorded, in detail, their overland travel to San Francisco and then by sea to French Polynesia and their service on the islands. In late 1852 the Crosbys returned to California, beginning what is probably the most historically significant part of her writings, her diaries of life. First, in immediately post Gold Rush San Francisco and, second, in the new Mormon village of San Bernardino in southern California. There is no comparable record by a woman of 1850s life in these growing communities. The Crosbys responded in 1857 to Brigham Young's call for church members to gather in Utah and again abandoned a new home, this the nicest one they had built, one of the finest houses in San Bernardino. Such unquestioning loyalty was a characteristic Caroline and Jonathan displayed again and again.--Provided by publisher.
Foreword / Maureen Ursenbach Beecher -- Editors' notes -- Introduction -- Youth to arrival in Salt Lake Valley: January 1807 to October 1848 -- Youth to marriage: memoirs, 1807 to October 1834 -- Conversion, baptism to arrival in Kirtland, Ohio: memoirs, November 1834 to January 1836 -- Kirtland to Pleasant Garden, Indiana: memoirs, January 1836 to June 1842 -- Nauvoo, Illinois: memoirs, June 1842 to September 1846 -- Across the plains to Salt Lake Valley: journal, 10 May to October 1848 -- Salt Lake Valley: memoirs, October 1848 to May 1850 -- To French Polynesia; return to San Francisco: May 1850 to September 1852 -- Overland journey to San Francisco, California: journal, 7 May to August 1850 -- San Francisco to French Polynesia and return: journal and memoirs, 16 August 1850 to 5 September 1852 -- Mission San Jose and San Francisco: September 1852 to November 1855 -- Mission San Jose, California: journal, 6 September 1852 to 20 January 1854 -- San Francisco, Horner's addition: journal, 21 January 1854 to 21 June 1855 -- San Francisco, the city: journal, 22 June to 23 November 1855 -- The San Bernardino years: November 1855 to December 1857 -- San Bernardino, a new home: journal, November 1855 to December 1856 -- San Bernardino-the final year: journal, January to December 1857.
Keywords: Crosby, Caroline Barnes, 1807-1884; Crosby, Caroline Barnes, 1807-1884 -- Diaries; Mormon pioneers -- West (U.S.) -- Biography; Mormon women -- West (U.S.) -- Biography; Frontier and pioneer life -- West (U.S.); Mormons -- West (U.S.) -- History -- 19th century; Salt Lake Valley (Utah) -- Biography; Middle West -- Biography; San Francisco (Calif.) -- Biography; San Bernardino (Calif.) -- Biography